Le biomasse lignocellulosiche - Maracchi, Giampiero; BONARI, Enrico (Strumenti per la didattica e la ricerca, 2015)
The volume presents a comprehensive analysis of the lignocellulosic biomass that can be produced by the agricultural industry. The first part describes the territorial and political framework of the production of renewable energies by the agricultural industry. The lignocellulosic chains are then introduced, in an analytical description of the main crops aimed at the production of biomass and agronomic cultivation techniques; moreover, the potential of the crop residues is analysed. Finally, the volume takes into account the aspects related to territorial suitability as well as economic and environmental sustainability.